Peran Internal Audit Dalam Meningkatkan Kinerja Perusahaan : (Studi Kasus Pada PT Garam) - Arizza Zulia R. J; IBK Bayangkara (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
Internal audit refers to an examination carried out by the company’s internal audit department. The traditional internal-audit paradigm has shifted from a compliance-oriented audit toward a value-added internal audit. In this evolved role, internal auditors do not just function as controllers, but serve as contributors of added value through strategic recommendations, improvement suggestions, and decision-making support. They play a crucial role in supporting corporate governance (GCG), risk management, and internal controls. Internal audit thus operates as an independent and objective internal control mechanism that helps identify risks, ensure regulatory compliance, and propose enhancements to operational and financial processes, ultimately strengthening company performance. This study employs a qualitative, case-study approach, using interviews and observations for data collection. The findings indicate that at PT Garam, the internal audit function has evolved no longer just as compliance overseer, but as a managerial partner actively involved in operational decision making.